Visualizing Cell Motility in Mouse Ear Explants. Issue 5 (9th May 2022) - Petrie, Ryan J.
Abstract: A method to visualize cell motility in fluorescence‐labeled mouse‐ear dermal explants is described. This approach allows cell and matrix dynamics to be visualized in physiologically relevant, three‐dimensional (3D) environments. This Basic Protocol for the preparation of mouse‐ear dermal explants can be optimized and applied to any tissue explant and cell type. © 2022 Wiley Periodicals LLC.